Mediated depictions of mental health, chronic care and literacy: a narrative analysis of Randall’s mental health journey in the television series, This is Us - Tenzek, Kelly E.; Lattimer, Tahleen A.; Heneveld, Kyle; Lapan, Emily; Neurohr, Madison; Gillis, Stephanie (Frontiers in Psychiatry, 2023)
Introduction Mental health and delivery of care is a global issue, that was only magnified by COVID-19. Over the past 3 years, people’s time spent watching television increased, while the way that mental health care was delivered changed. Audiences can gain insight into mental health issues through positive or negative mediated depictions on television. We argue that mental health is a chronic condition and the importance of literacy through different domains is critical for how the characters in media content and audience viewers make sense of mental health. Method The current study uses qualitative narrative analysis to examine the narrative probability and fidelity at the intersection of mental health depictions, the chronic care model, and different types of literacy in the award-winning series, This is Us. Results Findings reveal that Randall’s experiences with mental health (N = 38 episodes) depict moments of narrative coherence and fidelity to varying degrees. We see Randall’s experiences align most with the self-management support and community elements of the CCM, but the overall depiction is unbalanced. Randall’s literacy level is high, but if inspected on a deeper level, analysis points to differing levels of health and mental health literacy, thus enabling and constraining positive and realistic portrayals of mental health. Discussion Implications for mental health as a chronic issue and care delivery through CCM are discussed along with the importance of different types of literacy for audience members who may be struggling with a mental health disorder or trying to navigate the health care system. We offer recommendations for using Randall’s narrative as a teaching tool, integrating CCM into clinical visits to help guide delivery of care and understand literacy levels, and finally future work should continue this line of work from an Entertainment-Education perspective.